Survivorship care in head neck cancer - Shrikant B. Mali (Oral Oncology Reports)
Post-treatment follow-up in head and neck cancer (HNC) is limited to early identification of recurrent and second HNCs. Both cancer survivors and caregivers often experience a range of problems and unmet needs during post-treatment survivorship. Web-based dyadic interventions may be critical for cancer survivors and their caregivers. Survivors of oral cavity cancer who did not return to work had a worse physical and social-emotional function and required more tangible social support and positive social interactions. The poorer psychosocial adjustment was reported by patients with more severe facial disfigurement and less social support. Medical professionals may use these variables to identify higher-risk groups for early intensive intervention.